2021
DOI: 10.1080/21655979.2021.1971504
|View full text |Cite
|
Sign up to set email alerts
|

Enamel matrix derivative (EMD) enhances the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs)

Abstract: To investigate the EMD's capacity in BMSCs osteogenic differentiation. In vivo and in vitro, BMSCs were treated with EMD, scanning electron microscopy, and Alizarin Red staining were used to detect the changes in the osteogenic ability of BMSCs, and the proliferation ability of BMSCs was evaluated by CCK8. In addition, by adding xav939, a typical inhibitor of Wnt/β-catenin signaling pathway, the regulatory function of Wnt/β-catenin signaling was clarified. The results showed that EMD promote cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
6
0
2
Order By: Relevance
“…Bone marrow mesenchymal stem cells (BMSCs) are adult stem cells that play important roles in implant osseointegration processes [ 9 , 10 ]. Studies have shown that a high-glucose environment has a substantial negative impact on BMSC biological processes, such as cell proliferation and migration [ 11 ], and that glucose dose-dependently inhibits the osteogenic differentiation potential of BMSCs [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) are adult stem cells that play important roles in implant osseointegration processes [ 9 , 10 ]. Studies have shown that a high-glucose environment has a substantial negative impact on BMSC biological processes, such as cell proliferation and migration [ 11 ], and that glucose dose-dependently inhibits the osteogenic differentiation potential of BMSCs [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regenerative potential of EMD in the formation of new attachment has been confirmed by a plethora of RCTs and human histological as well as in vitro studies (Figure 5) [27][28][29][30][31][32][33]. Quite expectedly, the results of C2 are, therefore, in the range of the latest clinical trials investigating EMD heterografts [34,35].…”
Section: Discussionmentioning
confidence: 75%
“…OPN participates in bone formation and reconstruction by regulating the balance between osteoblasts and osteoclasts. Additionally, OPN, another osteoblast marker, plays an important role in the mineralization and absorption of bone matrix [ 39 ]. The presence of OCN reflects osteoblast maturation and not only objectively indicates the osteogenic function of osteoblasts but also reveals the state of bone formation and turnover.…”
Section: Discussionmentioning
confidence: 99%